2011
DOI: 10.1007/s00392-011-0383-3
|View full text |Cite
|
Sign up to set email alerts
|

Markers of oxidative stress after ablation of atrial fibrillation are associated with inflammation, delivered radiofrequency energy and early recurrence of atrial fibrillation

Abstract: Markers of oxidative stress showed a significant up-regulation during the first 2 days after AF ablation. Their up-regulation was linked to inflammation, delivered radiofrequency energy, and early recurrence of AF, but did not predict long-term ablation outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
1
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(47 citation statements)
references
References 36 publications
0
45
1
1
Order By: Relevance
“…Richter et al demonstrated that markers of oxidative stress linked to inflammation showed significant upregulation during the first 2 days after AF ablation and predicted a recurrence within 1 week post-ablation, but not the long-term outcome. 5 than in the RF group (37/41 vs. 28/41, P=0.014) during 11.0±3.2 months of follow-up. In the CB group, the success rate was significantly higher in the patients without ERAF than in those with it (24/24 vs. 13/17, P=0.012).…”
Section: Eraf After Rf and Cb Ablationmentioning
confidence: 96%
See 1 more Smart Citation
“…Richter et al demonstrated that markers of oxidative stress linked to inflammation showed significant upregulation during the first 2 days after AF ablation and predicted a recurrence within 1 week post-ablation, but not the long-term outcome. 5 than in the RF group (37/41 vs. 28/41, P=0.014) during 11.0±3.2 months of follow-up. In the CB group, the success rate was significantly higher in the patients without ERAF than in those with it (24/24 vs. 13/17, P=0.012).…”
Section: Eraf After Rf and Cb Ablationmentioning
confidence: 96%
“…[4][5][6] The aim of the present study was to prospectively compare (1) the proportion of patients with AF recurrence within the first 3 months post ablation procedure (ie, ERAF) using a 14-day consecutive monitoring system, (2) the timecourse patterns of biomarkers of myocardial injury, and inflammatory and prothrombotic biomarkers during the perioperative period, and (3) the factors associated with ERAF, in RF and 2nd-generation CB ablation patients with paroxysmal AF.…”
mentioning
confidence: 99%
“…Atrial tissue edema after RFCA has been reported to be related with early AF recurrence. 21) As the presence of tissue edema may prevent achieving sufficient energy to induce myocardial necrosis, electrical isolation between the LA and the pulmonary vein by RFCA could not be achieved effectively. Therefore, a longer ablation time could result in increased tissue edema, hence, longer ablation time was associated with AF recurrence in the short-term after ablation.…”
Section: Discussionmentioning
confidence: 99%
“…62 As the cytokines increase, the risk of AF concomitantly increases. Therefore, colchicine, a potent anti-inflammatory agent, may have a relevant role in preventing inflammatory-facilitated AF after catheter ablation.…”
Section: Maintenance Post Ablation Colchicinementioning
confidence: 99%